Employers' perception towards potential career opportunities among graduates of the Master of Science Technopreneurship Program - Mohamad, Armanurah; Abdullah, Rohani; Amir, Abdul Razak (ASEAN Universities Consortium of Entrepreneurship Education (AUCEE), 2010)
The marketability of the program is one of the important, factors that need to be considered by all higher learning institution before introducing any new program. Therefore, getting perceptions from employers about the program to be introduced will give a better picture of the marketability of the program. The purpose of this paper is to discuss the perceptions of employers towards potential career opportunities among graduates of Master of Science Technopreneurship offered by the University Utara Malaysia. This study has three main objectives. First is to explore and identify the potential fields that these graduates are able to contribute to the organization. Second is to examine the potential posts that are suitable for graduates of the technopreneurship program in the organization. Third is to identify the potential contribution and support from organization for the program. The survey is conducted among eight focus groups, namely the information technology (IT) entrepreneurs, non IT entrepreneurs, intrapreneurs, entrepreneurship guidance and training agencies, academics in the field of IT, academics in the field of entrepreneurship, bank and financial institutions, and, consultation and counseling firms. The analysis of the employers' perception towards graduates of technopreneurship is based on 39 respondents representing employers from the eight focus groups.